Administration of L. salivarius expressing 3D8 scFv as a feed additive improved the growth performance, immune homeostasis, and gut microbiota of chickens. (8th June 2020) - Sureshkumar, Shanmugam; Jung, Sun Keun; Kim, Dongjun; Oh, Keon Bong; Yang, Hyeon; Lee, Hwi Cheul; Jo, Yong Jin; Lee, Hae Sun; Lee, Sukchan; Byun, Sung June
Abstract: Probiotics have been defined as live microorganisms that are administered in an appropriate amount to provide health benefits to the host animal. In this study, we investigated the effect of L. salivarius DJ‐sa‐01 secreting the 3D8 single‐chain variable fragment (3D8 scFv) on the growth performance, cytokine secretion, and intestinal microbial flora of chickens. The experiment was divided into the control group and L. salivarius expressing 3D8 scFv experimental group. Chicken was fed 10 9 colony‐forming units (CFUs) of wild‐type (WT) L. salivarius or 3D8 scFv‐secreting L. salivarius daily for 35 days. The administration of L. salivarius expressing 3D8 scFv significantly improved the body weight of chickens compared with the administration of WT L. salivarius . A 16S ribosomal RNA metagenomic analysis showed that Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes were the dominant phyla in both experimental groups. At the genus level, Lactobacillus was more abundant (22.82%) in the L. salivarius/ 3D8 group compared with the WT L. salivarius group. The serum levels of cytokines, such as IL‐8, TNF‐α, IL‐1β, IFN‐γ, IL‐4, and IGF1, were significantly reduced in the L. salivarius /3D8‐treated chickens. In summary, our results suggest that L. salivarius expressing 3D8 scFv could be considered a feed additive for improving the growth performance, immune function, and disease resistance of poultry.